An innovation systems approach to enhanced farmer adoption of climate-ready germplasm and agronomic practices - Beuchelt, Tina; Camacho, Carolina; Govaerts, Bram; Donnet, Laura; Riis-Jacobsen, Jens; Hellin, Jonathon (International Food Policy Research Institute, 2014)
By 2050, climate change is likely to reduce maize production globally by 3–10 percent and wheat production in developing countries by 29–34 percent. Even without climate change, the real costs of wheat and maize will increase by 60 percent between 2000 and 2050; climate change could make the figure substantially greater. Food security, despite the above, may be possible if agricultural systems are transformed through improved seed, fertilizer, land use, and governance.